Voluntary Sustainability Standards and Social Network Development: The Unpredictable Impact Pathways to Achieving a Living Income Amongst Indonesian Coffee Farmers - Bray, Joshua G.; Neilson, Jeffrey; Arifin, Bustanul; Ismono, Hanung (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
This paper presents coffee producers’ subjective perceptions of voluntary sustainability standards (VSS) programs across southern Sumatra, a global center for Robusta coffee production. Household surveys and a series of farmer interviews revealed that producers generally had positive perceptions of these programs. Despite positive perceptions, the standards had little impact on yield or household incomes. This apparent paradox is explained by improved social networks and social capital, which were seen as important for broader livelihood security. Producers believed that VSS facilitated access to material support and increased knowledge exchange. This builds both bonding and bridging social capital, all with minimal disruption to the low-input system of coffee production that fits within farmers’ broader livelihood strategies. Our approach highlights the challenges that impact assessments (including applications of the living income concept) face when seeking to establish ostensibly objective measures of well-being.